Nova abordagem metodológica de modelagem computacional e determinação de áreas prioritárias para prospecção de fósseis da megafauna quaternária - Aragão, Wilcilene Santos de (2020)
The fossil discoveries of the quaternary megafauna in Sergipe began in 1884, occurring predominantly in outcrops of the tank type. Currently there are records of occurrences of herbivores of the species Catonyx cuvieri, Equus neogeus, Eremotherium laurillardi, Notiomastodon platensis, Pachyarmatherium brasiliense, Paleolama major, Toxodon platensis, in addition to indeterminate records of Glyptotherium and Mylodontidae. In the group of carnivores, the only species with occurrence for the state is Smilodon populator. Paleodistribution models can assist in the identification of regions with greater chances of past species occurrence and the combination of projections of these models with algorithms for prioritizing areas such as Zonation, can constitute a methodological framework applicable to fossil prospecting. The objective of this work is to determine regions with greater fossiliferous potential in Sergipe, through the use of species paleodistribution data, taphonomic biases, geomorphological information and use of the geographical spaces added to the Zonation software, and to compare with what is known in the literature for the State. The construction of paleodistribution models was performed using Maxent, an algorithm that combines occurrence records with spatialized climatic data for the preparation of climate suitability maps. The validation of these maps was done by analyzing the values of the AUC (AUC - Area Under the ROC Curve) metric. In the step of determining priority areas, Zonation was used, which combines the generated suitability maps with spatial data from cave records, elevation variation and rural density in Brazil. The 14 species studied presented models with good predictive performance (AUC> 0.75) enabling the use of maps obtained in Zonation. As a result, we obtained a single map with the areas most likely to occur fossiliferous for the entire set of species analyzed. Using the state of Sergipe as a reference, the areas mapped with high fossiliferous priority for the state corroborate the regions already known to have fossiliferous occurrences and which are available in the literature. Other areas where the occurrence of fossils is still unknown are potentially fossiliferous, and may be the target of future prospecting efforts, including as a means of validating the model presented. In view of the positive results obtained, it can be considered that this methodology is valid for other studies that have the same objective, and can serve as a consistent methodological framework for mapping priority areas for fossil prospecting. Future empirical studies will be important to refine the results of the proposed methodology, as well as to enable a more comprehensive validation of it.